NAVIGATING IDENTITY AND SOCIETAL EXPECTATIONS IN EASTERINE KIRE’S THE RESPECTABLE WOMEN (International Journal of Food and Nutritional Sciences, 2022)
Easterine Kire’s novel The Respectable Woman explores into the intricate interplay between identity, cultural expectations, and gender roles within Naga society. This research paper examines the protagonist's journey as she grapples with societal norms that define respectability and dictate her worth as a woman. Kire artfully navigates the tension between individual desires and communal expectations, highlighting the struggles faced by women in traditional contexts. The research underscores the broader implications of Kire’s work in the context of indigenous literature, contributing to discussions on cultural identity, gender dynamics, and the quest for personal autonomy. Through character analysis, the paper explores how familial and societal pressures shape the protagonist's identity, revealing a profound conflict between self-acceptance and societal validation.